Temporal Lobe Epilepsy and Psychiatric Comorbidity - Vinti, Valerio; Dell'Isola, Giovanni Battista; Tascini, Giorgia; Mencaroni, Elisabetta; Cara, Giuseppe Di; Striano, Pasquale; Verrotti, Alberto (Frontiers in Neurology, 2021)
Most focal seizures originate in the temporal lobe and are commonly divided into mesial and lateral temporal epilepsy, depending on the neuronal circuitry involved. The hallmark features of mesial temporal epilepsy are aura, absence and automatisms. Symptoms often overlap with the lateral temporal epilepsy. However, the latter present a less evident psychomotor arrest, frequent clonies and dystonic postures, and common secondary generalization. Sclerosis of the hippocampus is the most frequent cause of temporal lobe epilepsy (TLE). Other possible etiologies are tumors, alterations of cortical development, traumatic, infectious and vascular lesions. An additional form of lateral temporal epilepsy follows an autosomal dominant pattern of inheritance, which is caused in a third of cases by mutations in the genes LGI1 and Reelin. TLE is among all epilepsies the most frequently associated with psychiatric comorbidity. Anxiety, depression and interictal dysphoria are recurrent psychiatric disorders in pediatric patients with TLE. In addition, these alterations are often combined with cognitive, learning and behavioral impairment. These comorbidities occur more frequently in TLE with hippocampal sclerosis and with pharmacoresistance. Psychiatric comorbidities reduce considerably the quality of life of these children and their family. Thus, early detection and appropriate management and therapeutic strategies could improve the prognosis of these patients. The aim of this review is to analyze TLE correlation with psychiatric disorders and its underlying conditions.